2012
DOI: 10.1021/ml300144n
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 2-Alkyl-1-arylsulfonylprolinamides as 11β-Hydroxysteroid Dehydrogenase Type 1 Inhibitors

Abstract: On the basis of scaffold hopping, a novel series of 2-alkyl-1-arylsulfonylprolinamides was discovered as 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD-1) inhibitors. A representative compound 4ek, obtained through SAR and structure optimization studies, demonstrates excellent in vitro potency against 11β-HSD-1 and dose-dependent in vivo inhibition of 11β-HSD-1 in a prednisone/prednisolone transformation biomarker study in mice.KEYWORDS: metabolic syndrome, enzyme inhibitor, 11β-hydroxysteroid dehydrogenase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Mouse pharmacokinetics remained problematic with high clearance (60 mL min –1 kg –1 ) and low bioavailability (3%). A dose dependent reduction in mouse in vivo inhibition of 11β-HSD1 was demonstrated by dosing of 95 (3–30 mg/kg) by intraperitoneal dosing …”
Section: Medicinal Chemistry Of Inhibitors Of 11β-hsd1mentioning
confidence: 99%
“…Mouse pharmacokinetics remained problematic with high clearance (60 mL min –1 kg –1 ) and low bioavailability (3%). A dose dependent reduction in mouse in vivo inhibition of 11β-HSD1 was demonstrated by dosing of 95 (3–30 mg/kg) by intraperitoneal dosing …”
Section: Medicinal Chemistry Of Inhibitors Of 11β-hsd1mentioning
confidence: 99%
“…These and other preclinical findings build a strong case that inhibition of 11β-HSD1 may be an efficacious approach for the treatment of metabolic syndrome. As a result, much attention has been focused on the discovery and development of inhibitors of this enzyme. In clinical trials, Incyte, Merck, and others have demonstrated that 11β-HSD1 inhibitors improved glycaemic control, lipid profiles, and blood pressure with modest weight loss . In addition to this indication, we recently explored and proposed atheroprotection as an emerging indication for this target.…”
Section: Introductionmentioning
confidence: 99%
“…(R)-1-(tert-Butoxycarbonyl)-2-methylpyrrolidine-2-carboxylic Acid (3a). 19 A pressure reactor was charged with 5% Pd/C (2.56 g of 5% Pd/C, 3 wt %) and purged with nitrogen. The (R)-Boc-2methylproline benzyl ester (10a, 146.32 g of 59.4 wt %, 87.13 g = 272.79 mmol) was added, along with 426 mL of denatured EtOH.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%